Impact of Head Trauma: How MMA (Mixed Martial Arts) Affects the Sense of Smell, Cognition, and Quality of Life in Fighters - Durães, Guilherme Basso; Guerino, José Lucas Barbosa da Silva Bortoleto; Garcia, Ellen Cristine Duarte; Voegels, Richard Louis; Pinna, Fábio de Rezende; Fornazieri, Marco Aurélio (International Archives of Otorhinolaryngology, 2025)
The sense of smell plays an essential role in well-being, influencing relationships, the formation of emotional memories, and protection against toxic substances in food and the environment. Post-traumatic olfactory loss is among the leading causes of olfactory alterations, especially in contact sports like Mixed Martial Arts (MMA), which involve frequent physical trauma, particularly to the head. To date, the relationship between olfactory dysfunction and head trauma in fighters remains underexplored.To evaluate possible olfactory, gustatory, and cognitive dysfunctions in MMA fighters. Methods: Fourteen MMA fighters and 14 control participants, matched for sex and age, were recruited. The participants underwent tests to evaluate olfaction (Visual Analog Scale (VAS) and the University of Pennsylvania Smell Identification Test (UPSIT), taste (Modified Global Gustatory Test), cognition (Montreal Cognitive Assessment, MoCA) and quality of life (The 36-Item Short Form Health Survey questionnaire, SF-36).A statistically significant difference was found in olfactory function between the groups (p = 0.021), with fighters having a lower mean score than the control group (fighters: 28.5 ± 4.4 vs. controls: 31.8 ± 2.4). Additionally, MMA fighters showed cognitive decline and impairment in quality of life aspects. No difference was observed in gustatory function between the groups (p = 0.508).The results indicate that MMA fighters exhibit impairments in olfactory function, as well as in cognition and quality of life. Further studies with larger sample sizes are needed for a more in-depth analysis of the impact of this sport on athletes' lives.
Keywords: olfaction disorders; hyposmia; athletic injuries